Royalist women writers, 1650-1689 - Chalmers, Hero (Oxford English monographs., 2004)
Looking in detail at the work of Margaret Cavendish, Katherine Philips, and Aphra Behn, this work argues that their writings inaugurate a more assertive model of the Englishwoman as literary author, which is crucially enabled by their royalist affiliations.